2014
DOI: 10.18433/j3m89q
|View full text |Cite
|
Sign up to set email alerts
|

Organic Anion Transporting Polypeptides 1B1 and 1B3 Play an Important Role in Uremic Toxin Handling and Drug-Uremic Toxin Interactions in the Liver

Abstract: PURPOSE. Organic anion-transporting polypeptide (OATP) 1B1 and OATP1B3 contribute to hepatic uptake of numerous drugs. Thus, reduced OATP1B1 and OATP1B3 activity in chronic kidney disease (CKD) may have a major impact on the hepatic clearance of drugs. The effect of drug-uremic toxin interactions on OATP1B1 and OATP1B3 has not been well studied. In the present study, we examine the inhibitory effects of uremic toxins on OATP1B1 and OATP1B3 transport activity to evaluate the interactions between drugs and uremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…Microbiota-derived uremic toxins affect hepatic OATP1B1, OATP1B3, and OATP2B1 activity and expression [56,6771]. For example, OATP1B1 and OATP1B3 transport of methotrexate is inhibited by kynurenic acid, indole-3-acetic acid, indoxyl sulfate and p-cresol in HEK293 cells [68]. Kynurenic acid has the strongest inhibitory effect.…”
Section: Effects Of Microbial Toxins On Drug Transportersmentioning
confidence: 99%
“…Microbiota-derived uremic toxins affect hepatic OATP1B1, OATP1B3, and OATP2B1 activity and expression [56,6771]. For example, OATP1B1 and OATP1B3 transport of methotrexate is inhibited by kynurenic acid, indole-3-acetic acid, indoxyl sulfate and p-cresol in HEK293 cells [68]. Kynurenic acid has the strongest inhibitory effect.…”
Section: Effects Of Microbial Toxins On Drug Transportersmentioning
confidence: 99%
“…Indoxyl sulfate is a well‐known uremic toxin that interacts with organic anion transporters. Transport by SLC22A6, SLC22A8 and SLCO1B3 was determined using RP‐HPLC–UV (Enomoto et al, ), RP‐HPLC–FL (Fujita et al, ) and LC/ESI–MS/MS (Sato et al, ), respectively. From these studies, it is suggested that indoxyl sulfate is a substrate for not only renal transporters SLC22A6 and SLC22A8 but also hepatic transporter SLCO1B3.…”
Section: Transport Of Endogenous Compounds As Determined By Chromatogmentioning
confidence: 99%
“…From these studies, it is suggested that indoxyl sulfate is a substrate for not only renal transporters SLC22A6 and SLC22A8 but also hepatic transporter SLCO1B3. Kynurenic acid, which is a metabolite in the kynurenine pathway, was identified as a substrate for ABCC4, SLCO1B1 and SLCO1B3 using LC/ESI–MS/MS (Dankers et al, ; Sato et al, ; Table ). Transporter‐overexpressing membrane vesicles or cells were used for the assay.…”
Section: Transport Of Endogenous Compounds As Determined By Chromatogmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies attribute uremic toxins, metabolic byproducts that accumulate in uremia, as a major cause of reduced drug transporter function in CKD (Barreto et al, 2014;Masereeuw et al, 2014). Uremic toxins are believed to competitively inhibit drug transport and to downregulate transporter expression (Reyes and Benet, 2011;Sato et al, 2014). However, uremic toxins do not begin to accumulate until end-stage renal disease and therefore may only explain changes in drug transporter function in patients with end-state renal disease.…”
mentioning
confidence: 99%